Comparative study of dual 3‐phase permanent magnet machines with coil span of two slot‐pitches. Issue 12 (1st December 2021) - Feng, Jianghua; Xu, Peilin; Zhu, Ziqiang; Wang, Shensheng; Shao, Bo; Xiao, Yang; Guo, Shuying; Li, Yifeng; Feng, Shouzhi
Abstract: In this study, the electromagnetic performances of dual 3‐phase permanent magnet (PM) machines with coil span of two slot‐pitches are comparatively investigated. It mainly focuses on two PM machines with different slot/pole number combinations ( N s /2 p ), that is, the 24‐slot/10‐pole and 24‐slot/14‐pole machines (2 p = N s /2 ± 2). First, winding configurations are illustrated for these two dual 3‐phase machines with 30° angle displacement. Then, the winding factor, back electromotive force, average torque, torque ripple, iron and PM losses, short‐circuit (SC) current, and PM irreversible demagnetisation are analysed and compared for both machines on the conditions of healthy operation and one set of three‐phase fault, that is, SC or open circuit (OC), respectively. The comparative results show that on healthy condition the 14‐pole PM machine has a slightly larger torque output. Besides, on 3‐phase OC condition, the 14‐pole machine also performs better over‐rating torque capability. In terms of iron and PM losses, the 10‐pole machine has smaller iron losses but larger PM losses than the 14‐pole machine. Moreover, on 3‐phase SC condition, the 14‐pole machine has a significantly lower risk of PM irreversible demagnetisation than the 10‐pole machine, although both machines have very similar SC currents. Finally, the 24‐slot/10‐ and 14‐pole dual 3‐phase PM machines are both prototyped and some tests are carried out for validation.